2001
DOI: 10.1029/2000wr000151
|View full text |Cite
|
Sign up to set email alerts
|

Extended tailing of bacteria following breakthrough at the Narrow Channel Focus Area, Oyster, Virginia

Abstract: Abstract. Extended tailing of low bacterial concentrations following breakthrough at the Narrow Channel focus area was observed for 4 months. Bacterial attachment and detachment kinetics associated with breakthrough and extended tailing were determined by fitting a one-dimensional transport model to the field breakthrough-tailing data. Spatial variations in attachment rate coefficient (k f) were observed under forced gradient conditions (i.e., kf decreased as travel distance increased), possibly because of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 50 publications
2
81
3
Order By: Relevance
“…However, slow release of attached bacteria at low concentrations over long periods of time may contribute significantly to transport over longer distances. At the South Oyster site (NC flow cell), inferred detachment rate coefficients were similar in magnitude to attachment rate coefficients [139]. This contrasts to laboratory experimental results reported in the literature, in which estimated detachment rate coefficients are one to three orders of magnitude smaller than attachment rate coefficients [139, Table 2].…”
Section: Extended Tailing/detachmentcontrasting
confidence: 54%
“…However, slow release of attached bacteria at low concentrations over long periods of time may contribute significantly to transport over longer distances. At the South Oyster site (NC flow cell), inferred detachment rate coefficients were similar in magnitude to attachment rate coefficients [139]. This contrasts to laboratory experimental results reported in the literature, in which estimated detachment rate coefficients are one to three orders of magnitude smaller than attachment rate coefficients [139, Table 2].…”
Section: Extended Tailing/detachmentcontrasting
confidence: 54%
“…Recent modeling . A particle-based model (T. D. Scheibe, submitted for publication) is capable of incorporating these complexities into the model formulation and yielding a robust fit for both effluent breakthrough and the profile of attached bacteria in sediment (51). Differential advection.…”
Section: Discussionmentioning
confidence: 99%
“…At South Oyster, a dramatic increase in protozoan populations was observed in response to the injection of bacteria [20]. Although the total effect is difficult to quantify because of limited observations of attached protozoan populations, it was shown that an apparent increase in attachment rate coincided with the timing of the protozoan bloom at a time when a decrease in attachment rate would have been expected based on other factors [139].…”
Section: Predationmentioning
confidence: 99%
“…Note that pore exclusion is also termed specifically ''size exclusion'' by some authors [98], as well as various other terms such as ''volume exclusion'' [4], ''pore size exclusion'' [116], or ''size exclusion chromatography'' [50]. The term ''differential advection'' has also been introduced [138,139] to generally describe the phenomenon of earlier breakthrough of colloids relative to a solute tracer without specific regard to the mechanism. The mechanics and modeling of pore exclusion has been recently debated [44,98].…”
Section: Size Exclusionmentioning
confidence: 99%